Le tourisme balnéaire face à l’occupation anarchique du littoral : étude de cas des stations balnéaires de Cap Skirring et de Kafountine (Basse Casamance, Sénégal) - Sadou Bocoum (Études Caribéennes)
The economic stakes on the coasts are large and difficult to reconcile. Seaside tourism coexists with many other activities on the coast and each of them benefits. The cohabitation of tourism with other socio-economic activities (fishing, processing of fish products) on the coast is a constraint that weakens the development of the seaside type. In this context, this contribution aims to analyze the impacts of the anarchic occupation of activities on the coast on tourism, and to contribute to the reasoned development of this area of activity. It aims first to make a diagnosis of the occupation of the coastline of the seaside resorts of Cap Skirring and Kafountine and finally to analyze land pressures and conflicts of use on coastal tourism. This paper, beyond the cartographic approach that allowed to analyze the dynamics of land use, to understand the importance of activities on these seaside resorts, is based on a quantitative and qualitative approach (through questionnaires, interview guides, and observation) which allowed in part to analyze the perception of the population, tourism actors and tourists.The problem of development and the lack of organization of the actors noted on these spaces give rise to constraints that make the development of seaside tourism difficult. The results show that the deterioration of the quality of the coastline due to unsanitary conditions, congestion, the problem related to smoke and insecurity remain major factors that negatively affect the tourism of these destinations. In the same dynamic, 72% of tourists and 77% of those in charge of accommodation facilities considered the beach to be unhealthy. This situation is noticeable on the coast of the two municipalities through garbage dumps, rotten fish on the beach, and the proliferation of plastic bags. The results showed another problem which is that of smoke and congestion of the coast. This situation is favoured by the rapid increase in the number of traditional smoking rooms on the fishing docks. The hotels, camps, inns and residences that are located next to the fishing docks are disturbed by the importance of the fumes that emanate from these fish smokers and odors (drying, salting and smoking area). Thus, 68% of those in charge of accommodation facilities confirmed that seaside tourism cannot coexist with these fish processing activities because they pollute a lot and make this beach unfit.